Taxon- and Growth Phase-Specific Antioxidant Production by Chlorophyte, Bacillariophyte, and Haptophyte Strains Isolated From Tropical Waters - Rahman, Norazira Abdu; Katayama, Tomoyo; Wahid, Mohd Effendy Abd; Kasan, Nor Azman; Khatoon, Helena; Yamada, Yuichiro; Takahashi, Kazutaka (Frontiers in Bioengineering and Biotechnology, 2020)
Antioxidants found in microalgae play an essential role in both animals and humans, against various diseases and aging processes by protecting cells from oxidative damage. In this study, 26 indigenous tropical marine microalgae were screened. Out of the 26 screened strains, 10 were selected and were further investigated for their natural antioxidant compounds which include carotenoids, phenolics, and fatty acids collected in their exponential and stationary phases. The antioxidant capacity was also evaluated by a total of four assays, which include ABTS, DPPH, superoxide radical (O2•−) scavenging capacity, and nitric oxide (•NO−) scavenging capacity. This study revealed that the antioxidant capacity of the microalgae varied between divisions, strains, and growth phase and was also related to the content of antioxidant compounds present in the cells. Carotenoids and phenolics were found to be the major contributors to the antioxidant capacity, followed by polyunsaturated fatty acids linoleic acid (LA), eicosapentaenoic acid (EPA), arachidonic acid (ARA), and docosahexaenoic acid (DHA) compared to other fatty acids. The antioxidant capacity of the selected bacillariophytes and haptophytes was found to be positively correlated to phenolic (R2 value = 0.623, 0.714 and 0.786 with ABTS, DPPH, and •NO−) under exponential phase, and to carotenoid fucoxanthin and -carotene (R2 value = 0.530, 0.581 with ABTS, and 0.710, 0.795 with O2•−) under stationary phase. Meanwhile, antioxidant capacity of chlorophyte strains was positively correlated with lutein, -carotene and zeaxanthin under the exponential phase (R2 value = 0.615, 0.615, 0.507 with ABTS, and R2 value = 0.794, 0.659 and 0.509 with •NO−). In the stationary phase, chlorophyte strains were positively correlated with violaxanthin (0.755 with •NO−), neoxanthin (0.623 with DPPH, 0.610 with •NO−), and lutein (0.582 with NO−). This study showed that antioxidant capacity and related antioxidant compound production of tropical microalgae strains are growth phase-dependent. The results can be used to improve the microalgal antioxidant compound production for application in pharmaceutical, nutraceutical, food, and feed industry.